2017
DOI: 10.15761/lps.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Cystic artery lymph node-is it a fixed important landmark during cholecystectomy?

Abstract: Bile duct injury during laparoscopic cholecystectomy (LC) is rare and often happens due to misidentification. Experts recommend dissection during laparoscopic cholecystectomy occur lateral to the cystic artery lymph node (LN). The LN is classically identified as a single node overlying the cystic artery and lateral to the bile duct. It thus represents another important landmark during LC. We present the first patient, to our knowledge, with 3 LNs in the hepatobiliary triangle. The laparoscopic cholecystectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The node may not be solitary and uniformly present first reported some 50 years ago by Williams and Whittaker in 80 postmortem examinations [ 15 ]. A triple cystic artery lymph node has been reported [ 16 ]. Similar to our cystic artery LN excision rate of 18.7%, Katri et al intraoperatively identified the LN in 85.7% of LCs (126/147) and excided the LN in 20.6% (26/126) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The node may not be solitary and uniformly present first reported some 50 years ago by Williams and Whittaker in 80 postmortem examinations [ 15 ]. A triple cystic artery lymph node has been reported [ 16 ]. Similar to our cystic artery LN excision rate of 18.7%, Katri et al intraoperatively identified the LN in 85.7% of LCs (126/147) and excided the LN in 20.6% (26/126) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Controlling for surgeon case-mix, differences may be incomplete given the limited literature as to which factors influence LN excision. The frequency of multiple cystic artery lymph nodes is likely to be very low but is unknown [ 16 ], meaning that a small proportion of the patients may have had multiple nodes where one was left behind while the other excised and thus been classified as LN present. Some lymph nodes may have been purposefully excised, e.g., the surgeon was suspicious of the gallbladder or LN appearance – this number is likely very low.…”
Section: Discussionmentioning
confidence: 99%
“…El ganglio cístico se encuentra comúnmente cerca de la arteria cística, por lo tanto, este procedimiento de rescate sugiere identificar esta estructura e iniciar la disección lateralmente al ganglio para reducir el riesgo de lesión de vía biliar. (Woi Tiang et al, 2017). Aunque aún se desconoce si el ganglio se puede identificar durante cada colecistectomía ya que no hay reportes acerca de la constancia, así como de la presencia de más de un ganglio.…”
Section: Otras Opciones Descritas Sonunclassified